2005
DOI: 10.1002/pssa.200420064
|View full text |Cite
|
Sign up to set email alerts
|

Thermal effects in the size distribution of SiC nanodots on Si(111)

Abstract: We have used scanning tunneling microscopy (STM), Auger electron spectroscopy (AES) and X-ray Photoelectron spectroscopy (XPS) to investigate the formation of nanoscopic structures on Si(111), from wafers with a high bulk C concentration. The samples were prepared by long time thermal annealing of the silicon samples, followed by a high temperature flash in ultrahigh vacuum. An increased surface C concentration is induced by segregation from the bulk. The surface is found to roughen on the nanososcopic le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 23 publications
(12 reference statements)
0
3
0
Order By: Relevance
“…Not only will this process eventually lead to the complete decomposition of the oxide layer, it will also trigger a substantial roughening of the silicon surface itself, leading to the formation and growth of nanostructures at the initial void nucleation points in the oxide [3]. These nanostructures have been shown to grow in the form of silicon carbide (SiC) nanocrystals [4,5], which nucleate on the surface as a result of carbon contamination both from residual molecules in the vacuum chamber as well as impurity inclusions within the oxide [6].…”
Section: Introductionmentioning
confidence: 99%
“…Not only will this process eventually lead to the complete decomposition of the oxide layer, it will also trigger a substantial roughening of the silicon surface itself, leading to the formation and growth of nanostructures at the initial void nucleation points in the oxide [3]. These nanostructures have been shown to grow in the form of silicon carbide (SiC) nanocrystals [4,5], which nucleate on the surface as a result of carbon contamination both from residual molecules in the vacuum chamber as well as impurity inclusions within the oxide [6].…”
Section: Introductionmentioning
confidence: 99%
“…Several groups have attempted to synthesize SiC nanoparticles on wafers [4,5,9,10]. Xu et al [4] used RF plasma sputtering and a compound SiC target (Si:C ∼ 1:1) to deposit SiC nanoparticles on Si(100) substrates with AlN buffer layers at a substrate temperature of 350 • C for 1.0 h. Xu et al [5] applied low-energy mass-selected ion beam deposition (MSIBD) to select C + ions at 100 eV to bombard a 4 •off Si(111) substrate in order to grow nanosized SiC dots at temperatures of 800-950 • C. Kametani [9] reported that the CVD ferrocene (Fe(C 5 H 5 ) 2 ) precursor was used to form SiC nanodots on Si(111) substrates by deposition at 600 • C followed by annealing at 600-800 • C. Flores et al [10] reported that Si(111) substrates with high C content were annealed at 660-810 • C to form SiC nanodots by segregation of carbon atoms from the bulk to the surface and reacted with Si to form SiC nanodots. In this paper, a novel approach to the synthesis of SiC nanoparticles on Si(100) wafers using an ultra-high-vacuum ion beam sputtering process followed by vacuum thermal annealing is reported.…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, the higher deposition temperature (normally above750 °C) makes the landing carbon atoms energetically reacted with Si atoms on the surface and aggregated into large islands. The step edges are etched into irregular kinks . In our case, the deposition temperature is selected at about 600 °C.…”
mentioning
confidence: 99%